2019
DOI: 10.1002/etc.4587
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Exposure to 2,2′,3,5′,6‐pentachlorobiphenyl (PCB‐95) Causes Developmental Malformations in Zebrafish

Abstract: 2,2′,3,5′,6-Pentachlorobiphenyl (PCB-95) is an environmental neurotoxicant. There is accumulated evidence that some neurotoxic effects of PCB-95 are caused by increased spontaneous Ca 2+ oscillations in neurons resulting from modifying ryanodine receptors (RyR) in calcium-releasing channels. However, there are large gaps in explaining brain and other developmental malformations on embryonic PCB-95 exposure. In the present study, we address those deficiencies by studying the toxic effects of PCB-95 using zebraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…Our teratogenic results are consistent with previously published work that reported no malformations or mortality in larval zebrafish younger than 7 dpf statically exposed to PCB 153 at concentrations as high as 10 μM ( Aluru et al, 2020 ). However, our results differ from other studies that showed developmental exposures to PCB 95 caused malformations ( Ranasinghe et al, 2020 ). This discrepancy may reflect the different exposure paradigms employed between studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Our teratogenic results are consistent with previously published work that reported no malformations or mortality in larval zebrafish younger than 7 dpf statically exposed to PCB 153 at concentrations as high as 10 μM ( Aluru et al, 2020 ). However, our results differ from other studies that showed developmental exposures to PCB 95 caused malformations ( Ranasinghe et al, 2020 ). This discrepancy may reflect the different exposure paradigms employed between studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The zebrafish maintenance protocol and all of the reagents used are shown in Table S1. The dose concentrations were referenced from previous studies and confirmed with preliminary exposure experiments. As shown in Table , three doses of chemicals (high, medium, and low doses) were used in the embryo exposure experiments, wherein the medium- and low-dose concentrations were mostly comparable to those reported in environmental water samples. The in vivo concentrations of the chemicals were also determined in the exposed embryos to confirm that they matched the environmentally relevant concentrations (Table ).…”
Section: Methodsmentioning
confidence: 85%
“…Previous research has demonstrated that zebrafish larvae exposed to MPs, Cu, prednisolone, PCB-95, and combined exposures of Cu and MPs exhibit abnormal behavior during early developmental stages. These abnormalities manifest as either a lack of significant avoidance response towards visual stimuli or reduced avoidance behavior [ 49 , 88 , 89 ].…”
Section: Quick Approaches For Assessing Ocular Toxicitymentioning
confidence: 99%